GAYA PENDAMPINGAN TRANSPOSISIONAL SEBAGAI STRATEGI PASTORAL PENDIDIKAN DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI PAPUA: - Donatus Wea; Erly Lumban Gaol; Alexander Silaen; Yonarlianto Tembang (Jurnal Masalah Pastoral, 2026)
This research is motivated by the low learning achievement of students in Papua caused by the gap between the national education approach and the local socio-cultural context. Therefore, this study aims to: identify the implementation of transpositional mentoring in Catholic schools in Papua; analyze the factors that support and hinder its implementation; and test the effect of transpositional mentoring on improving student learning achievement. This study uses a mixed methods approach, with a descriptive qualitative and quasi-experimental quantitative design. Qualitative data were obtained through in-depth interviews, participant observation, and focus group discussions in five Catholic schools in South Papua, Highland Papua, and Central Papua with a total of 85 informants. Quantitative data were obtained through a Nonequivalent Control Group design on 150 students at the Santo Mikhael Catholic Junior High School in Merauke who were divided into experimental and control groups. Data analysis was conducted using an interactive model and descriptive and inferential statistical tests. The results of the study indicate that transpositional mentoring has been implemented practically through contextualization of teaching materials, the use of local language and culture, relational mentoring, experiential learning, critical reflection, and curriculum adaptation. Key supporting factors include teachers' pedagogical commitment, cultural proximity, relational culture, institutional support, and community involvement, while inhibiting factors include limited conceptual understanding, administrative pressure, limited resources, cultural distance, and low learning motivation. Quantitatively, transpositional mentoring has been shown to significantly improve learning achievement. Thus, transpositional mentoring is an effective, contextual, and transformative learning strategy for improving student achievement in Papua. This approach needs to be systematically integrated into education policies and teacher professional development.